Meta Analysis: The Effect of Social Support in Preventing Postpartum Depression in Postpartum Mothers - Meita Tyas Nugrahaeni; Niken Yuliani Untari; Nindita Arum Veibiani (Journal of Epidemiology and Public Health, 2022)
Background: Depression is one of the contributors to the disease that is the focus of public health in the world. The most common depression is postpartum depression. The postpartum period is a period of adaptation between mother and baby to optimize bonding attachment, so they need physical, emotional, and mental support from partners, families, and socially. This study was aimed to estimate the magnitude of the incidence of postpartum depression in postpartum mothers with the influence of social and family support, with a meta-analysis of the main study conducted by previous authors. Subjects and Method: This was a systematic review and meta-analysis with PICO, population: postpartum mothers. Intervention: strong social support. Comparison: weak social support. Outcome: postpartum depression. The articles used were obtained from several databases, namely Google Scholar, Pubmed, SpingerLink and Science Direct. Search keywords for articles were “Postnatal Depression” OR “Postpartum Depression” AND “Family Support” OR “Social Support” AND “Postpartum Mother”. The inclusion criteria for research articles were full-text articles using a cross-sectional observational study design, postpartum mothers who received intervention in the form of family and social support, the results of the study were postpartum/postnatal depression, multivariate analysis with Adjusted Odds Ratio (aOR) to measure estimates effect. Data were analyzed using the Review Manager application (RevMan 5.3). Results: A total of 10 cross-sectional articles were selected for a systematic review and meta-analysis with 8,930 postpartum mothers from Asia and Africa. Mothers giving birth without social support can contribute to the worsening of the postpartum mother's condition to cause postpartum depression (OR= 3.12; 95%CI 1.95 to 4.99; p= 0.009). Conclusion: Social support can increase the prevention of postpartum depression in postpartum mothers. Keywords: social support, postpartum mother, postpartum depression, postnatal depression Correspondence: Meita Tyas Nugrahaeni. Faculty of Public Health, Universitas Airlangga. Jl. Dr. Ir. H. Soekarno, Mulyorejo, Kota Surabaya 60115, East Java, Indonesia. Email: meitatyas04@gmail.com. Mobile: 085974825459.